Pengaruh Penggunaan Gadget dan Kedisiplinan Siswa Terhadap Prestasi Belajar PAI Kelas V SDN Kutisari II Surabaya - Munawwir, Munawwir; Faizah, Rizka Maulidah; Rif’ah, Siti Nailur; Basyiroh, Laila Alfin; Safitri, Nurul Jannah; Maharani, Alissa Putri; Ramadhany, Angie Wulan (Universitas Pahlawan Tuanku Tambusai, 2024)
According to Suwarsih, the intense use of gadgets causes a loss of interest in other activities and affects brain development that lead to discipline. Discipline is the main requirement that students must have in the learning process to achieve good performance. This study focuses on the effect of the use of gadgets and discipline on the learning outcomes of class V at SDN Kutisari II Surabaya which aims to determine the impact of gadgets and discipline on student learning outcomes. This research uses non-experimental research with quantitative descriptive methods. Data collection techniques used in this study using questionnaires, interviews, and documentation. Data analysis in this study uses descriptive statistics that are used to describe and describe the data that has been collected. The results of the research findings (1) there is a significant positive effect between discipline on learning achievement. (2) there is a significant influence between the use of gadgets on learning achievement. (3) there is a significant positive effect between discipline and the intensity of using gadgets together on learning achievement.